Neoadjuvant chemotherapy followed by concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in locoregionally advanced nasopharyngeal carcinoma: A phase III multicentre randomised controlled trial. (April 2017) - Cao, Su-Mei; Yang, Qi; Guo, Ling; Mai, Hai-Qiang; Mo, Hao-Yuan; Cao, Ka-Jia; Qian, Chao-Nan; Zhao, Chong; Xiang, Yan-Qun; Zhang, Xiu-Ping; Lin, Zhi-Xiong; Li, Wei-Xiong; et al.
Abstract: Background: The role of neoadjuvant chemotherapy (NACT) for locoregionally advanced nasopharyngeal carcinoma (NPC) is unclear. We aimed to evaluate the feasibility and efficacy of NACT followed by concurrent chemoradiotherapy (CCRT) versus CCRT alone in locoregionally advanced NPC. Methods: Patients with stage III–IVB (excluding T3N0-1) NPC were randomly assigned to receive NACT followed by CCRT (investigational arm) or CCRT alone (control arm). Both arms were treated with 80 mg/m 2 cisplatin every 3 weeks concurrently with radiotherapy. The investigational arm received cisplatin (80 mg/m 2 d1) and fluorouracil (800 mg/m 2 civ d1–5) every 3 weeks for two cycles before CCRT. The primary end-point was disease-free survival (DFS) and distant metastasis-free survival (DMFS). Secondary end-point was overall survival (OS). Survival curves for the time-to-event endpoints were analyzed by the Kaplan–Meier method and compared using the log-rank test. The P value was calculated using the 5-year endpoints. Results: Four hundred seventy six patients were randomly assigned to the investigational (n = 238) and control arms (n = 238). The investigational arm achieved higher 3-year DFS rate (82.0%, 95% CI = 0.77–0.87) than the control arm (74.1%, 95% CI = 0.68–0.80, P = 0.028). The 3-year DMFS rate was 86.0% for the investigational arm versus 82.0% for the control arm, with marginal statistical significance (P = 0.056). However, there were no statistically significant differences in OS or locoregional relapse-free survival (LRRFS) rates between two arms (OS: 88.2% versus 88.5%, P = 0.815; LRRFS: 94.3% versus 90.8%, P = 0.430). The most common grade 3–4 toxicity during NACT was neutropenia (16.0%). During CCRT, the investigational arm experienced statistically significantly more grade 3–4 toxicities (P < 0.001). Conclusion: NACT improved tumour control compared with CCRT alone in locoregionally advanced NPC, particularly at distant sites. However, there was no early gain in OS. Longer follow-up is needed to determine the eventual therapeutic efficacy. Highlights: The role of neoadjuvant chemotherapy (NACT) in locoregionally advanced nasopharyngeal carcinoma (NPC) was undetermined. We undertook a phase III multicentre randomised controlled trial to investigate the added value of NACT. Our studies showed that NACT could improve tumour control in locoregionally advanced NPC, particularly at distant sites.